Studi Etnografi Virtual Belajar Daring Dan Penanggulangannya - Mudzamil, Dody (LUGAS Jurnal Komunikasi, 2022)
Because of the impact of the Covid-19 case in Indonesia, school activities that should be carried out face-to-face are now carried out online. Information exchange activities and conversational interactions between students and teachers are now carried out online, but this is a new phenomenon in Indonesia.In light of these considerations, the purpose of this study is to 1) determine the issues that obstruct communication in online learning activities at SMP Negeri 266 and SMP Shahid 1 in North Jakarta, as well as to understand 2). establish what kind of response educational institutions make when it comes to dealing with noise in online learning. Based on the opinion of O'rourke (2019: 2) regarding communication management, a procedure of studying changes in communication habits would be adopted, followed by the opinion of Pavlik and Mcintosh (2011: 256), then followed by the Cyber Media Analysis process (Nasrullah, 2018: 45). The Interpretive-Ethnographic Virtual Approach Method was used in this study; this paradigm focuses on a person's experience of a social problem that exists in the community, while Virtual Ethnography is a method used in researching communication culture that occurs in cyberspace. Data collection techniques used in this study were observation, interview, and document analysis, and the nature of the data used were primary and secondary data. The study's findings include the detection of various communication barriers at the beginning of the online learning program, such as device ownership issues, and the accommodation of existing problems by the school supervisor, who will then assess and find a solution with the school.